A Cross Country Analysis of Banking Efficiency: East Asian Banks - Cao, S (2013)
The objective of this paper is to examine the cost efficiency of Asian banks through a cross country analysis—Japan, Singapore, South Korea, Hong Kong and Taiwan. In order to achieve the objective, cost efficiency for the sample of banks over the period of 1998—2012 is estimated using stochastic frontier approach (SFA) following the suggestion of Aigner, Lovell and Schmidt (1977). The model employed in this paper is the one of Battese and Coelli (1995). It provides the estimation of cost efficiency in a single stage while analysing the impact of some country specific characteristics on the banking cost efficiency. The results indicate that banks overall exhibit a cost efficiency score of 0.7223. Among the five countries, Japan is the most cost efficient one with the score of 0.7659 while Hong Kong has the lowest efficiency of 0.4876. It also shows that country-specific characteristics have significant influences on cost efficiency. The results, which provide the sources of inefficiency, may provide useful insights for bankers and policy makers to improve decision-making process and policy establishment.